2015
DOI: 10.1371/journal.pbio.1002125
|View full text |Cite|
|
Sign up to set email alerts
|

Dynamic Endothelial Cell Rearrangements Drive Developmental Vessel Regression

Abstract: Patterning of functional blood vessel networks is achieved by pruning of superfluous connections. The cellular and molecular principles of vessel regression are poorly understood. Here we show that regression is mediated by dynamic and polarized migration of endothelial cells, representing anastomosis in reverse. Establishing and analyzing the first axial polarity map of all endothelial cells in a remodeling vascular network, we propose that balanced movement of cells maintains the primitive plexus under low s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
424
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 266 publications
(447 citation statements)
references
References 34 publications
(48 reference statements)
22
424
1
Order By: Relevance
“…We did not find evidence at any stage of plexus resolution that would suggest that remodeling is accomplished through breakage and regression of epithelial segments, as reported for vascular plexus remodeling (Franco et al 2015). Rather, we observed an apparent progressive consolidation of epithelial plexus segments that effectively reduces the complexity of, and eventually eliminates, the plexus web to generate the final ductal tree.…”
Section: Distinct Processes Of Plexus-to-duct Remodeling and Epithelisupporting
confidence: 49%
“…We did not find evidence at any stage of plexus resolution that would suggest that remodeling is accomplished through breakage and regression of epithelial segments, as reported for vascular plexus remodeling (Franco et al 2015). Rather, we observed an apparent progressive consolidation of epithelial plexus segments that effectively reduces the complexity of, and eventually eliminates, the plexus web to generate the final ductal tree.…”
Section: Distinct Processes Of Plexus-to-duct Remodeling and Epithelisupporting
confidence: 49%
“…36,37 Recent detailed analysis of the angiogenic retinal vasculature in mice found that only~5% of regressing vessels found during normal angiogenesis actually contained apoptotic ECs. 38 Whether EC apoptosis is functionally necessary for vessel pruning in the mouse retina is yet to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…A further distinction between types of vasoregression has been proposed, dependent on the persistence of a patent lumen of the regressive capillary branch (type 1 pruning, closed lumen, resulting from low shear stress/non-perfusion; type 2 pruning, open lumen, high shear stress/perfusion). In this context, blood flow is a critical determinant, since vasoconstriction induces vasoregression while enhanced blood flow protects against vasoregression [28,29].…”
Section: The Importance Of Vasoregressionmentioning
confidence: 99%